Dampak Kepuasan Pelayanan, Kepercayaan Pelanggan Dan User Experience Yang Mempengaruhi Loyalitas Pelanggan Pada Platform E-Commerce Di Kalangan Generasi Z (STIE Mahardhika Surabaya) - Yulia Eka Tata Pramadita; Tri Wahjoedi; Safa’at Safa’at; Evi Thelia Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The aim of this research is to investigate the impact of service quality, trust from consumers, and user experience on how loyal customers are to online shopping sites, specifically for Generation Z. The study uses a quantitative approach, ghatering information through an online survey with 88 Gen Z participants who have used e-commerce sites in the past six months. The analysis of the data was carried out using multiple linear regression techniques. The results suggest that service quality, consumer trust, and user experience has the strongest effect (β = 0.45, p < 0.05), followed by consumer trust (β = 0.38, p < 0.05), and then service quality (β = 0.32, p < 0.05). This model explains 67% of the differences in customer loyalty (R² = 0.67). The theoretical contribution of the study enhances the understanding of customer loyalty in the online environment, particularly concerning Generation Z. Practically the findings can help e-commerce businesses boost customer loyalty by enhancing user experience, building trust, and improving service quality.